The Algal Polysaccharide Ulvan Induces Resistance in Wheat Against Zymoseptoria tritici Without Major Alteration of Leaf Metabolome - de Borba, Marlon C.; Velho, Aline C.; Maia-Grondard, Alessandra; Baltenweck, Raymonde; Magnin-Robert, Maryline; Randoux, Béatrice; Holvoet, Maxime; Hilbert, Jean-Louis; Flahaut, Christophe; Reignault, Philippe; Hugueney, Philippe; Stadnik, Marciel J.; et al. (Frontiers in Plant Science, 2021)
The present study aims at examining the ability of ulvan, a water-soluble polysaccharide from the green seaweed Ulva fasciata, to provide protection and induce resistance in wheat against the hemibiotrophic fungus Zymoseptoria tritici. MALDI-TOF-MS analysis indicated that ulvan is mainly composed of unsaturated monosaccharides (rhamnose, rhamnose-3-sulfate, and xylose) and numerous uronic acid residues. In the greenhouse, foliar application of ulvan at 10 mg.mL-1 two days before fungal inoculation reduced disease severity and pycnidium density by 45% and 50%, respectively. Ulvan did not exhibit any direct antifungal activity towards Z. tritici, neither in vitro nor in planta. However, ulvan treatment significantly reduced substomatal colonization and pycnidium formation within the mesophyll of treated leaves. Molecular assays revealed that ulvan spraying elicits but does not prime the expression of genes involved in several wheat defense pathways, including pathogenesis-related proteins (β-1,3-endoglucanase and chitinase), reactive oxygen species metabolism (oxalate oxidase), and octadecanoid pathway (lipoxygenase and allene oxide synthase), while no up-regulation was recorded for gene markers of the phenylpropanoid pathway (phenylalanine ammonia-lyase and chalcone synthase). Interestingly, quantification of 83 metabolites from major chemical families using UHPLC-MS, in both non-infectious and infectious conditions, showed no substantial changes in wheat metabolome upon ulvan treatment, suggesting a low metabolic cost associated with ulvan-induced resistance. Our findings provide evidence that ulvan confers protection and triggers defense mechanisms in wheat against Z. tritici without major modification of the plant physiology.